A Critique of the Cultural Authenticity of Arabic Young Adult Literature - M. Anati, Nisreen (Sciences humaines; Vol. 27 (2012): SCIENCES HUMAINES, 2014)
لعل هذه الدراسة هي الأولى من نوعها لأنها تعلن  ظهور الأدب العربي الخاص بالمراهقين العرب (باللغة الانجليزية ) – نصوص أدبية موجه الى الاطفال الذين تتراوح أعمارهم 12 -20 سنة. ألاهم من ذلك , تُحدد هذه الدراسة ولأول مرة معايير و خصائص النصوص الادبية " الاصيلة ثقافياً". و بالاضافة الى ذلك, فإن الدراسة  ُتسلط  الضوء على قيمة دمج هذه النصوص الادبية في مناهج اللغة ألانجليزية في البلدان الناطقة باللغة العربية وغير الناطقة بالعربية.   This paper is the first in its kind as it declares the emergence of Arabic Young Adult Literature (in English) as an independent genre - literature texts written about Arab children ages 12-20. More importantly, this study establishes, for the first time, a teacher-friendly criterion of the key characteristics of “culturally authentic” Arabic young adult texts. Additionally, the study highlights the value of integrating Arabic Young Adult Literature (AYAL) texts (in English) into the English language arts curriculum in Arabic and non-Arabic speaking countries.